Reliability and Cross-Cultural Validation of the Turkish Version of the Visual Function Classification System (VFCS) for Children with Cerebral Palsy. - Adiguzel Tat, H.; Karadeniz, P. Gunel; Apaydin, U.; Efkere, P. Atalan; Ergun, N; Elbasan, B. (Developmental Neurorehabilitation, 2024)
Purpose: This correlational study aimed to determine the reliability and validity of the Turkish version of the Visual Function Classification System (VFCS) for children with CP. Method: Two physiotherapists and caregivers (n = 56) applied the VFCS (n = 120) two times at a 15-day interval. Physiotherapists' classifications were compared for interrater reliability. Same physiotherapists and caregivers' classifications' were compared for intrarater reliability. Expanded & Revised Gross Motor Function Classification System (GMFCS E&R), Manual Ability Classification System (MACS), and Communication Function Classification System (CFCS) were used for assessing validity of the culturally adapted VFCS. Results: The interrater reliability between physiotherapists was excellent (ICC = 0.974, ICC = 0.988), while interrater reliability between the first physiotherapist and caregivers was good (ICC = 0.866, ICC = 0.893). The intrarater reliability was excellent (ICC = 0.971, ICC = 0.996, ICC = 0.984). A correlation was detected between the VFCS and the GMFCS E&R, MACS, and CFCS levels (r = 0.415, p <.001, r = 0.450, p <.001, r = 0.491, p <.001). Conclusion: The findings of this study demonstrate the utility, compatibility and reliability of the Turkish version of the VFCS. Trial registration number: NCT05102955